ANALISIS MISALIGNMENT CITRA MULTISPEKTRAL TERHADAP CITRA PANKROMATIK PADA DATA WORLDVIEW-2 - Brahmantara, Randy Prima; Kustiyo, Kustiyo (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2018)
The standard data of Worldview-2 owned by LAPAN is Ortho-Ready Standard level 2 (OR2A) data consisting of 4 multispectral bands (blue, green, red, NIR) and one panchromatic band each 2 m and 0,5 m spatial resolution. Both images have different metadata and RPC, making it possible to perform geometric corrections separately. This paper discusses the analysis of the inaccuracies of multispectral image positions to panchromatic images compared to those that have been systematically geometric corrected. The method used is fast fourier transform phase matching by taking 500 binding points between the two images. The measurement results prove that the multispectral image of the Worldview-2 data of the OR2A level has a larger shift compared with multispectral image that has been systematically geometric corrected. The multispectral image of the OR2A data shifts are 2,14 m on the X-axis and 0,42 m on the Y-axis. While the multispectral image that has been systematically geometric corrected shifts are 1,72 m on the X-axis and 0,54 m on the Y-axis.